THE USE OF MEMORY TRAINING APPLICATION FOR MEMORY REHABILITATION OF ELDERLY WITH DEMENTIA USING MONTESSORI-BASED ACTIVITIES - Opas, Pitchaporn; Arunsirot, Nutreutai; Pattarawongthana, Jarunee; Boonyarittanon, Ninooch (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2024)
This research aimed 1) to establish a memory training application for memory rehabilitation of elderly with dementia using Montessori-based activities, 2) to investigate the memory scores before and after the trial of the mentioned memory training application for memory rehabilitation of elderly with dementia, and 3) to examine the satisfaction of elderly with dementia towards the mentioned memory training application for rehabilitating their memory. The sample group consisted of 100 elderly who were selected using purposive sampling method. They were required to have education from elementary school onwards, and be able to help themselves. Moreover, they had to be screened by implementing the Thai Mental State Examination (TMSE) and the result scores must be less than 23 points. The research instrument for treatment was the memory training application for memory rehabilitation of elderly with dementia using Montessori-based activities, whereas the research instruments for collecting data were TMSE and a satisfaction questionnaire on the use of the memory training application for memory rehabilitation of elderly with dementia using Montessori-based activities. The data were statistically analyzed for mean and standard deviation. The researchers developed an application called “Brain Booster” on the Android operating system. The findings showed that after using the memory training application for memory rehabilitation of elderly with dementia using Montessori-based activities, the memory score of the elderly with dementia was significantly higher than before the experiment at the .01 level. Moreover, the overall satisfaction of the participating elderly was at a high level, with the mean of 4.44 and the standard deviation of 0.53. In addition, it was observed that most of the elderly had fun playing the brain training games from the application. Besides, the application was designed to be easy to use and uncomplicated, so it did not cause problems in using the application for the elderly.